2011
DOI: 10.1007/s10548-011-0203-0
|View full text |Cite|
|
Sign up to set email alerts
|

The Impact of a Regular Blood Donation on the Hematology and EEG of Healthy Young Male Blood Donors

Abstract: The aim of this study was to investigate the effect of 400 ml whole blood donation on the human electroencephalogram (EEG) and hematology, not earlier reported in the literature. EEG activity was recorded from ten male blood donors (experiment group) before, during and after blood donation (i.e., 400 ml whole blood withdrawal). EEG topography and regional spectral field powers analyses were carried out via fast Fourier transformation. The venous hemoglobin (Hb) concentration was measured with a hematology anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 36 publications
0
2
1
Order By: Relevance
“…Our previous study showed during blood donation, alpha-1 at the parietalfrontal area on human EEG-DMN transiently with no lasting effect at the post-donation period. 31 In this study, the reverse process of cerebral blood supply did not observe alpha-1 alterations but alpha-2 changes, even alpha-2 did not attain statistical differences. Similar changes existed in delta band spectra, delta intensity was increased in the pre-LVAS group compared with the control group, and the changes were attenuated in the post-LVAS group, which were in accordance with previous cerebral stroke patients EEG alteration.…”
Section: Discussioncontrasting
confidence: 50%
“…Our previous study showed during blood donation, alpha-1 at the parietalfrontal area on human EEG-DMN transiently with no lasting effect at the post-donation period. 31 In this study, the reverse process of cerebral blood supply did not observe alpha-1 alterations but alpha-2 changes, even alpha-2 did not attain statistical differences. Similar changes existed in delta band spectra, delta intensity was increased in the pre-LVAS group compared with the control group, and the changes were attenuated in the post-LVAS group, which were in accordance with previous cerebral stroke patients EEG alteration.…”
Section: Discussioncontrasting
confidence: 50%
“…After data collection, the EEG was analyzed offline with EEG lab 14.0 software as Zhang et al described[ 20 , 21 ]. Briefly, all EEG data were filtered offline with a 0.5–100 Hz bandpass filter for analysis.…”
Section: Methodsmentioning
confidence: 99%
“…The level of hemoglobin is another reason to consider blood transfusions (1). There is however a risk of misleading results if hemodilution has not yet been completed (9). In these cases, transfusions are not always a straightforward decision.…”
Section: Introductionmentioning
confidence: 99%